Transparency in monetary policy - Hermann Remsperger; Andreas Worms (Goethe University Frankfurt, Center for Financial Studies (CFS), 1999)
For some time now the buzzword 'transparency' has been bandied about in the media almost daily. For example, calls were made for greater transparency in the financial system in connection with developments in the Asian financial markets. But the call for greater transparency goes far beyond the financial markets. It is now regarded as a necessary part of good governance demanded of all economic policy makers. As the World Bank's chief economist Joseph Stiglitz put it: 'No one would dare say that they were against transparency (....): It would be like saying you were against motherhood or apple pie.' This paper focuses on transparency in monetary policy, in particular with respect to the European System of Central Bank.
urn:nbn:de:hebis:30-9654
Keywords: E58; 330; transparency; monetary policy; ESCB